TINJAUAN LITERATUR: PENINGKATAN KETAHANAN API DAN SIFAT MEKANIK PADA KOMPOSIT POLIMER DENGAN PENAMBAHAN BAHAN LIMBAH GEOPOLIMER - Afandi, Ridwan; Nurdin, Akhmad; Hastuti, Sri; Darsono, Febri Budi; Paundra, Fajar (Steam Engineering, 2024)
Composite polymers are now under development and are widely used in automobile manufacturing for interior panels, door panels, and bodywork. The research and development of polymer composites for the automobile manufacturing must have resilient fire resistance requirements. Currently, polymer composites with fire resistance capabilities have been developed with geopolymer materials, which offer benefits and produce excellent performance. Geopolymers are inorganic polymers that contain aluminosilicates, silica oxides, and alumina oxides. They have thermally resistant mechanical characteristics. Geopolymer materials are commonly derived from waste materials, including those utilized as additions to polymer composite materials, specifically coal fly ash and clay-based waste. The purpose of this literature is to discuss the path and progress of waste-based polymer reinforced composite technology for fire resistance. The methodology employed in this study takes a conceptual approach to articles on the influence of adding different types of geopolymer materials on the fire resistance properties of natural fiber reinforced composites. According to the findings, articles involving the inclusion of geopolymer materials tend to lower resistance to tensile and flexural stresses, whilst the addition of this geopolymer material reduces fire resistant qualities.